The Effect of Abusive Supervision on Employee Silence using Emotional Exhaustion and Organizational Justice as a Mediation Variable - Pangestu, Ragil Nunut; Wulansari, Nury Ariani (Universitas Negeri Semarang, 2019)
The purpose of this study to determine the effect of abusive supervision on employee silence with emotional exhaustion and organizational justice as a variable mediation. The population in this research is employees of textile and garment companies in Semarang Distcrict which is growing rapidly. Methods of data collection using observation, interviews and questionnaires. Sampling technique using multistage cluster sampling technique and the number of sample were 199. Methods of data analysis using descriptive analysis and collected data were analyzed by using WarpPLS software version 6.0. The results showed that abusive supervision had a positive and significant effect on the employee silence. Emotional exhaustion and organizational justice can mediate the relationship between abusive supervision on employee silence.